2020
DOI: 10.2807/1560-7917.es.2020.25.24.1900527
|View full text |Cite
|
Sign up to set email alerts
|

A common source for a trichinellosis outbreak reported in France and Serbia in 2017

Abstract: License, supplementary material and copyright This is an open-access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0) Licence. You may share and adapt the material, but must give appropriate credit to the source, provide a link to the licence and indicate if changes were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Nowadays, most outbreaks involve consumption of raw meat of infected game or pigs from small suburban farms and backyards ( Diaz et al, 2020 ). Trichinellosis outbreaks were observed for example in Eastern Europe in the early 1990s and early 2000s ( Djordjevic et al, 2003 ; Kurdova-Mintcheva et al, 2009 ; Neghina, 2010 ) as well as in Belgium in 2014 and in France and Serbia in 2017 ( Barruet et al, 2020 ; Messiaen et al, 2016 ). Reasons were amongst others laxity in veterinary control over meat production for economic reasons and high-risk animal production practices such as feeding of food waste or exposure to carcasses of swine or wildlife ( Poizo, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most outbreaks involve consumption of raw meat of infected game or pigs from small suburban farms and backyards ( Diaz et al, 2020 ). Trichinellosis outbreaks were observed for example in Eastern Europe in the early 1990s and early 2000s ( Djordjevic et al, 2003 ; Kurdova-Mintcheva et al, 2009 ; Neghina, 2010 ) as well as in Belgium in 2014 and in France and Serbia in 2017 ( Barruet et al, 2020 ; Messiaen et al, 2016 ). Reasons were amongst others laxity in veterinary control over meat production for economic reasons and high-risk animal production practices such as feeding of food waste or exposure to carcasses of swine or wildlife ( Poizo, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…This outbreak shows that travelling to endemic regions is the simple way of acquiring trichinellosis. Therefore, travelers to endemic regions should be aware of a risk of consuming untested homemade raw meat products bought outside of official market in countries where the prevalence of trichinellosis is high [43].…”
Section: Discussionmentioning
confidence: 99%
“…In France, human trichinellosis incidence is low, with only 68 cases reported from 2001 to 2016 in which more than half were related to the consumption of infected meat abroad or illegally imported meat [ 10 ]. Recently, Barruet et al (2020) reported an outbreak of 20 cases in Paris, France, in 2017 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%